Atypical cells in a voided urine cytology specimen in a renal transplant recipient. Issue 1 (16th September 2016) - Lu, Miao; Ho, Julie; Azordegan, Nazila; Perry, Anamarija M.; Gibson, Ian W.; Baker, Patricia
Abstract : Voided urine is routinely collected from renal transplant patients to screen for polyomavirus. In rare cases, atypical lymphoid cells can be detected in voided urine and raise the suspicion of post‐transplant lymphoproliferative disorder (PTLD). However, further immunohistochemistry of the cell block and flow cytometry is frequently limited by the low cellularity and poor preservation of voided urine. Therefore, PTLD of the renal allograft is usually diagnosed from tissue biopsy or nephrectomy specimens. Herein, we report a rare case of atypical cells in a voided urine cytology specimen from a kidney transplant recipient. Needle core biopsy of the renal allograft showed monomorphic PTLD. Diagn. Cytopathol. 2017;45:69–72. © 2016 Wiley Periodicals, Inc.